Correlates of visuospatial ability among older people in Indonesia - The Maria Meiwati Widagdo; Novia Bella Rianto; Restyandito; Erick Kurniawan (Wolters Kluwer Medknow Publications, 2021)
Introduction: The Indonesian elderly population keeps increasing. Aging is related with degeneration process, one of which is a decrease in cognitive function, including visuospatial ability. This is the first study on the visuospatial ability of Indonesian older people. Objective: This research aimed to assess the visuospatial ability and its correlation with sex, age, education, and general cognitive function among older people in Indonesia. Subjects and Methods: The research subjects were older people aged ≥60 years with Mini-Mental State Examination (MMSE) score ≥24. The visuospatial ability was assessed using Wechsler Adult Intelligence Scale-Revised (WAIS-R) Block Design Test (BDT). Regression analysis was performed to reveal the correlation of sex, age, education, and global cognitive function with visuospatial ability. Results: Sixty older people participated in this research, with an average age of 68.08 ± 6.24, mean MMSE score of 27.43 ± 1.71, and mean WAIS-R BDT score of 27.8 ± 7.27. The female and older individuals tended to have lower scores. Subjects with higher education and global cognitive function had higher WAIS-R BDT scores. Regression analysis showed that age and sex did not have significant effect, but education and global cognitive function had positive effect on visuospatial ability. Conclusion: There is a significant correlation between education and global cognitive function with visuospatial ability among older people in Indonesia.